Peningkatan Soft Skill untuk Menumbuhkan Kepercayaan Diri Anak SMK di Panti Asuhan Yatim Piatu Al Ikhwaniyah, Jurang Mangu Barat, Tangerang Selatan - Amanda, Riska; Cahya Wulandari, Suci; Delu Kaka, Sofia; Rizka Akbar, Irfan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The Student Creativity Program (PKM) aims to improve soft skills to foster the confidence of vocational school children at the Al Ikhwaniya Orphanage, West Mangu Gorge, South Tangerang. The problems found are the low courage of students in communicating, lack of ability to work together, and lack of experience in developing their potential. This activity was carried out through several stages, namely identification of needs, preparation of training modules, implementation of interactive workshops, communication simulations, and evaluation of participant development. The method used is a participatory training approach with role play activities, group discussions, and hands-on practice. The results of the activity showed an increase in communication skills, teamwork, and confidence of participants in expressing opinions and making decisions. This program is expected to be a model for sustainable soft skill development for orphanage children in facing educational and work challenges